(untitled) (FUDMA JOURNAL OF SCIENCES, 2025)
The paper briefly examined the trend of forest administration in Nigeria from the pre-colonial era to date. It examined it vis-a-vis forest policy formulation and review in the country. Presently, there is no separate forest policy in Nigeria but the administration of forest resources in the country is executed by the three tiers of government: the Federal, State and Local. Most of the authorities over forest resources are vested in the hands of the State government. Regrettably, the governments at all tiers have not paid much attention to forestry activities in the country. Inadequate staffers, poor remunerations, inadequate funding and corruption are some of the challenges facing forest administration and management in Nigeria. Most recently, the activities of encroachers/squatters, armed herdsmen, terrorists groups, kidnappers etc have caused a lot of destruction and depletion of our forests resources. These have affected forest administration and sustainable forest management in Nigeria. The paper, therefore, recommended the need for an urgent passage and approval of a separate policy for forestry, as has been done successfully in some of our neighbouring countries. This will positively affect the planning and execution of forestry programmes and activities in the country; more funding of forestry activities; improve security in our forest reserves to flush out criminals and other illegal settlers; the recruitment of well-trained and experienced forest personnel into the various forests organizations and agencies and the involvement of relevant stakeholders in the development, planning and implementation of forestry activities.